Penerapan Konsep Rainwater Harvesting di Kampus X Bandung - Eka Wardhani; Aldi Prasetya Triatmaja (Fakultas Teknik, 2022)
Over time, Campus X experienced rapid growth and needed additional space for the teaching and learning process. Space development will have an impact on increasing water demand. Campus X is located in the red zone of groundwater so it cannot increase the discharge of groundwater extraction. soil. This study aims to calculate the need for clean water in Campus X in 2030 as well as to calculate the potential for harvesting rainwater as an alternative source of clean water. The research method refers to the Regulation of the Minister of Public Works No. 11 of 2014 concerning the management of rainwater on buildings and their plots. Based on the results of the study, the population on Campus X in 2030 was 7,608 people with a water requirement of 368.38 m3 /day. There is an increase in the need for clean water by 38.62 m 3 /day compared to 2021. The application of rainwater harvesting with catcment area m2 is 14,036 and rainfall intensity of 165.47 mm/hour rainwater discharge of 52,704 m3/rainy day. Improving the quality of rainwater can be done by simple water treatment using an active sand filter unit.